Unique cyclophosphamide doses in male mice decrease the spermatic quality and germinal epithelium - Acosta, Láyonal (2012)
Cyclophosphamide (CP) is an alkylating agent commonly used as antineoplastic and immunosuppressive drug. The use of CP in the treatment of cancer is limited due to its severe toxicity. The aim of this study was to determine theeffectof a single dose of CP (220 mg/kg b.w.) intraperitoneally administered after 7 days,on sperm parameter and male germinal epithelium in mice. We used C57BL mature male mice divided into 2 groups (n= 10); Control Group (C): 0.9% and NaCl Treatment group (T): CP to 220 mg/kg cw in single dose. After 8 days all the mice were euthanized. The weight of the body and reproductive organs: testis, epididymis and vas deferens, were registered. Concentration, motility and sperm morphology and testicular histology were evaluated. Significant differences were found in body weight (student t-test p<0.05) (T: 20.18±1.9 g vs C: 23.35±1.2 g; testicular weight (T: 59.71±5.40 mg vs C: 72.90±2.8 mg), epididymis tail weight (T: 9.83 ± 1.54 vs C: 14.30 ± 2.20, vas deferens weight (T: 8.27±0.80 mg vs C: 10.61±0.76 mg respectively), concentration (T: 9.2±1.9 vs. C: 14.4±3.3 x 106 sperm / mL), progressive motility (T: 25.98±6,4% vs C: 42.96±5.2%). There wasn´t significant differences in sperm morphology (student t-test p<0.05), but there was a significant increase in abnormal tail and immature sperm (T vs. C: 36,24±7,8% vs 31.73±9,1%; 27,44±2,1% vs 18,51±8,6%; respectively) and also severe damage seminiferous tubules was observed. We conclude that single dose of CP (220mg/kg b.w.) decreased the reproductive quality of male mice.